Obese patients who fall have less injury severity but a longer hospital stay than normal-weight patients. Issue 1 (December 2016) - Chuang, Jung-Fang; Rau, Cheng-Shyuan; Liu, Hang-Tsung; Wu, Shao-Chun; Chen, Yi-Chun; Hsu, Shiun-Yuan; Hsieh, Hsiao-Yun; Hsieh, Ching-Hua
Abstract Background The effects of obesity on injury severity and outcome have been studied in trauma patients but not in those who have experienced a fall. The aim of this study was to compare injury patterns, injury severities, mortality rates, and in-hospital or intensive care unit (ICU) length of stay (LOS) between obese and normal-weight patients following a fall. Methods Detailed data were retrieved for 273 fall-related hospitalized obese adult patients with a body mass index (BMI) ≥30 kg/m2 and 2357 normal-weight patients with a BMI <25 kg/m2 but ≥18.5 kg/m2 from the Trauma Registry System of a Level I trauma center between January 1, 2009, and December 31, 2013. We used the Pearson's chi-squared test, Fisher's exact test, the Mann WhitneyU test, and independent Student'st -test to analyze differences between the two groups. Results Analysis of AIS scores and AIS severity scaling from 1 to 5 revealed no significant differences in trauma regions between obese and normal-weight patients. When stratified by injury severity (Injury Severity Score [ISS] of <16, 16–24, or ≥25), more obese patients had an ISS of <16 compared to normal-weight patients (90.5 % vs. 86.0 %, respectively;p  = 0.041), while more normal-weight patients had an ISS between 16 and 24 (11.0 % vs. 6.6 %, respectively;p  = 0.025). Obese patients who had experienced a fall had a significantly lower ISS (median (range): 9 (1–45)vs. 9 (1–50), respectively;p  = 0.015) but longer in-hospital LOS than did normal-weight patients (10.1 daysvs. 8.9 days, respectively;p  = 0.049). Even after taking account of possible differences in comorbidity and ISS, the obese patients have an average 1.54 day longer LOS than that of normal-weight patients. However, no significant differences were found between obese and normal-weight patients in terms of the New Injury Severity Score (NISS), Trauma-Injury Severity Score (TRISS), mortality, percentage of patients admitted to the ICU, or LOS in the ICU. Conclusion Obese patients who had experienced a fall did not have different injured body regions than did normal-weight patients. However, they had a lower ISS but a longer in-hospital LOS than did normal-weight patients.